An alien fish threatens an endangered parasitic bivalve: the relationship between brook trout (Salvelinus fontinalis) and freshwater pearl mussel (Margaritifera margaritifera) in northern Europe. Issue 6 (11th January 2016) - Salonen, Jouni K.; Marjomäki, Timo J.; Taskinen, Jouni
Abstract: Host–parasite interactions may play a significant role in biological invasions: for example, an invader may benefit from lower infectivity by native parasites in competition against the native hosts ('enemy release hypothesis'). The invasive North American brook trout ( Salvelinus fontinalis ) is replacing the native salmonid hosts of the freshwater pearl mussel (FPM, Margaritifera margaritifera ) in northern Europe, but the suitability of brook trout as a host for FPM is poorly known. In this study its suitability was investigated using an array of laboratory and field experiments, and several FPM populations from a catchment in northern Finland. The occurrence of brook trout in FPM rivers in the area was also studied. There were differences with respect to numbers and size of FPM larvae among the fish exposed to FPM, but generally brook trout was an unsuitable host or was clearly a poorer host for FPM than the native European salmonids, brown trout ( Salmo trutta ) or Atlantic salmon ( Salmo salar ). However, in one river a few FPM glochidia remained encysted in wild brook trout for at least 9 months, suggesting successful development – the first observation of its kind in Europe. A tendency was found for higher occurrence of brook trout in brown trout rivers with FPM than in brown trout rivers without FPM, being consistent with the enemy release hypothesis: as FPM infection is costly to the host, a higher glochidial load in brown trout may offer a competitive advantage to brook trout in FPM rivers. Generally, these results indicate that northern European FPM populations cannot typically use brook trout as their host fish. Therefore, the invasion and dispersal of brook trout, potentially leading to the disappearance of native salmonids, should also be considered as a potential threat to the endangered FPM populations. Copyright © 2016 John Wiley & Sons, Ltd.